Online Communities: An Intersection Between Computer-Mediated Communication, Subcultures and the Presentation of Self in the Global Age - Yousry, Fallon (Université d'Ottawa / University of Ottawa, 2018)
There has been extensive literature on the subject of subcultures in the fields of criminology and sociology. The term has undergone decades upon decades of revisions and debate amongst scholars. Despite the vast amount of literature available on the term subculture, there is unfortunately no clear-cut definition of what a subculture is, especially after what many sociologists referred to as the Post-Subcultural Turn. While that is problematic in and of itself, the term subculture still has yet to be framed and understood in light of recent technological advancements and strides towards globalization. This thesis will attempt to shed light on the muddled conceptions of the term subculture, as well as expanding subcultural theory to include subcultural engagement in online settings. Chapter 1 will provide a chronological account of the term subculture, including many of its evolutions, revisions and interpretations based on different schools of thought. Chapter 2 will follow up by discussing many of the criticisms directed at past conceptualizations of subculture, and where the term subculture should be heading with regards to expanding its conceptualization without conflating it with other terms. Chapter 2 will finish by suggesting a new path towards conceptualization by adapting subculture to include how subcultures are being formed and maintained through the use of the Internet. To make sense of subcultures using social networking sites in future chapters, Chapter 3 will delve into some of the main technological developments of the Internet including computer-mediated communication, social networks, and how they function as virtual conduits for facilitating social interactions and the spread of knowledge. Chapter 4 will pick up from Chapter 3 by discussing deviance in online settings, as well as introducing a new Goffmanian approach to understanding the presentation of self in online settings. Lastly, Chapter 5 will seek to answer three main questions about subcultures and their existence in online settings: 1. How do social networking sites operate as virtual conduits for the presentation of self? 2. How do subculturalists use social networking sites to create a sense of online community and membership? 3. How do subculturalists employ presentation of self strategies? These questions will be answered by employing an adapted Goffmanian approach to the presentation of self in online settings while also rethinking the concept of subcultural style. Lastly, this thesis will seek to provide guidance on where gaps in the literature still exist and can be explored in the near future.
Keywords: subculture; community; online community; computer-mediated communication; blogs; presentation of self